Determinants of Rural Household Food Security Status in North Shewa Zone, Amhara Region, Ethiopia. (12th April 2022) - Fikire, Abebaw Hailu; Zegeye, Mesele Belay
Abstract : Food insecurity is one of the most serious problems in developing countries, especially in Ethiopia. Therefore, it is important to understand the barriers to improving the state of food security in the country. Thus, this study aims to investigate the determinants of food security of rural households in the North Shewa zone in the Amhara region, Ethiopia. A sample of 796 farm households was considered. This paper used the calorie intake method per day to measure household food security status and a logit model to investigate the determinants of food security. The results show that family size, age of the household head, educational level of the head, off-farm activities, monthly income of the household, and distance from the market are the major determinants of rural household food security in the North Shewa Zone. The findings suggest that expanding the access to education in farm households, expanding the access to off-farm activities to increase household income, and expanding market access to farm households are important to improve rural food security status in the study area.